Underutilizing of SMK ( R) Durion Guiing's School Library and the ways of overcoming students' interest using the school library facilities / Siti Asiah Abd. Rahman - Abd. Rahman, Siti Asiah (2002)
Utilizing the school library facilities is one of the strategies that has been suggested to raise the students’ academic performance. The general aim of this study therefore is to find out ways to overcome the problems pertaining to the underutilize of the school library The study begin with the history of the library, library'today, school library and the students’ reason for not using the school library. It will also expose the advantages of using the library. The instrumentation used is a questionnaire, interviews and observation on student’s reactions.